Vergleichende Untersuchung der Einzelhandelsstrukturen der Städte Bursa, Kiel und London/Ontario - Stewig, Reinhard (ERDKUNDE, 1974)
The structure of retail trade in the Islamic-Oriental city of Bursa turned out to consist of a simple, two-fold gradation. While the mass of retail establishments for various needs is concentrated in the bazaar area, a great number of small retail centres for everyday needs is spread throughout the rest of the city. In contrast to this structure the retail pattern of the West European city of Kiel showed a four-fold gradation of centres. Besides the concentration of retail shops of various size in the innermost city-area and the small retail centres for daily needs there are first rank subcentres, which particularly distribute textiles, shoes and household goods, and second rank subcentres, which particularly offer chemist/dispensary, dry cleaning, and banking services. In the North American city of London/Ontario there appears to be a reduction in the steps of gradation in comparison to Kiel. One level of retail centre is represented both by the retail trade in the central business district and the shopping centres in the fringe areas of the city. The other, lower level is represented by the small variety and convenience store or store cluster for daily needs. The various gradations as well as the spatial arrangement of the respective retail centres within the cities must be interpreted in the light of a high degree of economic and social homogeneity on a low (Bursa) or high (London/ Ontario) level and of greater differentiation in Kiel. A genetic sequence, a cyclic development or evolution is suggested.